DNA Markers for Food Products Authentication - Daria Scarano; Rosa Rao (Diversity, 2014)
Media constantly refer of unscrupulous producers that adulterate, alter or replace premium products in food chains with the goal to maximize illegally profits. Food traceability is a central issue for the identification of improper labeling of processed food and feed and there are rules aimed to protect consumers and producers against fraudulent substitution of quality products in food chain, but the tools available are not always appropriate. DNA-based markers proved very effective for fresh and processed food molecular authentication. In this review, we illustrate potential and limits of different DNA markers focusing on low, medium and high-throughput markers, in order to monitor the genetic identity of food components in meat, fish and plants net-chains.